Quest for knowledge - Abd Razak, Dzulkifli (2005)
DURING the Abbasid rule, with the exception of the literary texts, Greek works were reintroduced as part of the remarkable new Arabic culture of learning, and later that of Andalusia. According to Professor Maria Rosa Menocal of Yale University, in her book The Ornament in the World, it was in alAndalus that the profoundly "Arabised" Jews rediscovered and reinvented Hebrew. It was also in alAndalus that the Christians embraced nearly every aspect of Arabic style — from intellectual style of philosophy to the architectural styles and game of chess — not only while living under Islamic domination but especially after wresting political control from them. The word "Arabised" is used to acknowledge that the Andalusians did a great deal more than merely learn to speak the language.